Three new species of Scalida (Blattodea: Blattellidae) from Yunnan, China - Qiao, Limin; Li, Qianqian; Yao, Wenwen; Wang, Zongqing; Che, Yanli (Zootaxa, 2023)
Three new Scalida species from Yunnan are reported: Scalida hamata Qiao & Che sp. nov., Scalida spinosa Qiao & Che sp. nov., Scalida ramiformis Qiao & Che sp. nov.. Morphological descriptions of the new species, including the male genitalia, are provided along with detailed photographs. A list and a key to species of Scalida in the world are provided.